Pathologic and therapeutic insights into cholestatic liver disease-associated depressive disorder - Xin Li; Hong Wang; Yufei Li; Menghao Huang; Xiaojiaoyang Li; Zongzhan Yu; Pengfei Li; Runping Liu (Acta Materia Medica)
The prevalence of depressive-like behavior is significantly higher in patients with cholestatic liver disease, leading to a notable reduction in the quality of life. This situation underscores the urgent need to investigate the mechanisms underlying the association between cholestasis and clinical depression. This review provides a comprehensive examination of how neuroendocrine disorders resulting from cholestasis influence the onset of depression through both direct and indirect mechanisms. First, how the accumulation of bile acids in the central nervous system (CNS) during cholestasis leads to damage to the blood-brain barrier, neuroinflammation, and neurodegeneration is discussed, highlighting the key roles of bile acid receptors, such as FXR and TGR5, in this process. Additionally, the gut-brain axis has been shown to be involved in the development of brain diseases in a variety of ways. Therefore, the indirect indirect effects of bile acids via the gut-brain axis, which affect the composition of the gut microbiota, the integrity of the gut barrier, and the secretion of gut hormones are summarized, thereby regulating the development of depression. However, whether bile acids can directly enter the CNS and which targets are targetable within the gut-brain axis remain pivotal questions. Addressing these issues will open new avenues for developing more effective therapeutic strategies aimed at alleviating depressive symptoms experienced by patients with cholestasis.